Comparative analysis of web application interfaces with buttons in graphical and text form for universal design - Kaliszuk, Jakub; Osmulska, Adriana; Plechawska-Wójcik, Małgorzata; Dzieńkowski, Mariusz (Journal of Computer Sciences Institute, 2022)
The purpose of this article is to compare application interfaces with buttons in graphical and text form. For the needs of the research, a web application was prepared with the functionality to change the form of buttons. The analysis of the availability of the application was performed using the WAVE tool. A research group of 10 students was prepared for the eyetracking experiment and form. The surveys conducted on the eyetracker allowed to assess which version of the interface enables faster and correct execution tasks. LUT’s list was used to test the quality of the designed interface.